NEGOTIATING LEARNING AND ACADEMIC ADAPTATION IN INTEGRATIVE ISLAMIC HIGHER EDUCATION: EXPERIENCES OF THAI INTERNATIONAL STUDENTS IN INDONESIA - Ismail Ismail; Silviatul Hasanah; A.M Wibowo; Joko Tri Haryanto (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2026)
This study aims to explore the academic adaptation challenges experienced by Thai international students at UIN Walisongo Semarang, Indonesia. A qualitative case study design was employed to capture participants' lived experiences. Data were collected through in-depth interviews and participant observation involving Thai international students and were analysed using the interactive model of Miles and Huberman, encompassing data condensation, data display, and conclusion drawing with continuous verification. The findings reveal that students encountered interconnected challenges in understanding Indonesian academic language, engaging with analytical and critical learning practices, participating in classroom discussions and presentations, meeting Indonesian academic writing standards, utilising digital learning resources such as the Learning Management System (LMS), digital libraries, and electronic journals, and establishing effective academic communication with lecturers and local students. These challenges demonstrate that academic adaptation extends beyond academic competence to include adjustment to learning culture, academic norms, interaction patterns, and technology-supported learning within an integrative Islamic higher education environment. Students gradually negotiated these demands through continuous engagement with the university's academic ecosystem while maintaining their cultural identity. This study contributes to the international higher education literature by proposing that academic adaptation in Islamic universities should be understood as a multidimensional process shaped by the integration of academic, cultural, technological, and religious dimensions rather than by academic factors alone. The findings provide practical implications for developing comprehensive institutional support programmes for international students in Islamic higher education.